The effect of Triton X surfactants on Pb (II) transport rate using bulk liquid membrane systems - Suljkanovic, Mersiha; SuljagiÄ‡, Jasmin; PaÅ¡iÄ‡, Mustafa (International Journal of Advanced Chemistry, 2021)
Implementation of the "bulk liquid membrane" (BLM) system was investigated in terms of its efficiency for selective removal of heavy metal ions from natural resources and industrial wastewater. In this paper, the removal of lead (II) ions through a liquid membrane system and factors that influence the process were examined. The research was performed using the homemade transport cell. Two organic solvents were used as liquid membranes: 1,2-dichloroethane and chloroform. Metal ion concentration in aqueous phases was monitored by flame atomic absorption spectrophotometry, after 4 hours of experiment. Macrocyclic ether (dicyclohexano-18-crown-6) was used as ligand for Pb (II) ions. The effects of nonionic surfactants (Triton X-100, Triton X-45 and Triton X-405) added in the receiving phase of BLM system were investigated. The results showed significant increase in transport rate compared to systems without surfactants. Considering the surfactant structure, transport rate of Pb (II) ions followed the order: TX-100 >TX-45>TX-405. Presence of TX-100 increased transport of Pb (II) ions up to 78% through chloroform and 58% through 1,2-dichloroethane.Â Â